2017
DOI: 10.1186/s12873-017-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of acute burns diagnosis made using smartphones and tablets: a questionnaire-based study among medical experts

Abstract: BackgroundRemote assistance for burns by medical experts can support nurses and general physicians in emergency care with diagnostic and management advice. Previous studies indicate a high diagnostic accuracy based on images viewed on a computer screen, but whether image-based analysis by experts using handheld devices is accurate remains to be determined.MethodA review of patient data from eight emergency centres in the Western Cape, South Africa, revealed 10 typical cases of burns commonly seen in children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Finally, a single study found somewhat limited utility of remote visual diagnostics in pediatric burn patients. Remote specialists had highly accurate total body surface area (TBSA) estimates but poor depth assessments [ 25 ]. All nine studies concluded that mobile health decision support interventions were an effective means to improve EC in LMICs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a single study found somewhat limited utility of remote visual diagnostics in pediatric burn patients. Remote specialists had highly accurate total body surface area (TBSA) estimates but poor depth assessments [ 25 ]. All nine studies concluded that mobile health decision support interventions were an effective means to improve EC in LMICs.…”
Section: Resultsmentioning
confidence: 99%
“…The four studies [25][26][27][28] of the thesis [29] took place when an app for acute burns was under development, intended to be used between emergency care nurses and physicians and burns experts in Western Cape province, South Africa [10,11]. The app was based on local initiatives and went through a long process of development in close collaboration with local stakeholders from burns and emergency medicine.…”
Section: Diagnostic Support From Clinical Experts Through Mhealthmentioning
confidence: 99%
“…An application of the context of emergency care of burns (text in red) in light of the congruence model (adapted from [30]) and the four studies focusing on the work of experts. [26] and third [27] study examined image quality and diagnostic accuracy in relation to assessment of burns using smartphone or tablet.…”
Section: Enhanced Understanding Through the Congruence Modelmentioning
confidence: 99%
See 2 more Smart Citations